Influence of Networking on Starts-Up Development in Incubation Hubs - Joe Kumbirai Karambakuwa; Mohamed Sayeed Bayat (CV. Literasi Indonesia, 2023)
This study on the role of networking in entrepreneurial incubation hubs was aimed at validating the influence of networking on start-up development in Harare, Zimbabwe. The research targeted start-up founders that had gone through the process of incubation in Harare. The study used a qualitative research method. A case study approach was then adopted in which the participants were purposively selected. An interviewing guide was used to gather data. The study involved three focus groups with a total of twenty-one start-up founders. The research established that start-ups tend to develop better through the infusion of ideas and experiences either through peer-to-peer or peer-to-coach or vice versa. Networking in incubation hubs aided learning as incubates had the chance to learn among themselves. The interaction created lifelong learning exposure which proved to be effective in creating personal development. In conclusion, it was found that networking forms a fundamental basis for start-up business success as it provides the bedrock for collaborations and the sharing of ideas that aids in the development of startups.